Giant Soft Tissue Sarcoma of Scalp with Skull and Cerebral Invasion - Yelamanchi, Raghav; Manjunath, Parikshith; Gupta, Nikhil; Durga, CK (Nepal Medical College Journal, 2021)
Scalp soft tissue sarcomas (STS) are very rare accounting for less than 0.1% of all malignancies. We report a rare clinical image of advanced stage soft tissue sarcoma of the scalp. A 65 year woman had presented to the surgical department with complaints of a rapidly growing swelling over the scalp for three months. On examination there was huge 20 x 20 cm swelling over the scalp in the left temporoparietal region with variegated consistency. Computed tomography of head revealed a large soft tissue mass with necrosis invading the bone and underlying brain parenchyma. Histopathological finding from core needle biopsy revealed pleomorphic sarcoma. STS are highly malignant tumors which should be diagnosed and treated using multimodality approach. Recurrences are common even after complete resection and prognosis is poor.